Determination of the absolute configuration of (+)- and (−)-N-CBZ-3-fluoropyrrolidine-3-methanol using vibrational circular dichroism and confirmation of stereochemistry by conversion to (R)-tert-butyl 3-fluoro-3-(((R)-1-phenylethyl)carbamoyl)pyrrolidine-1-carboxylate. Issue 24 (31st December 2016) - Procopiou, Panayiotis A.; Hatley, Richard J.D.; Lynn, Sean M.; Copley, Royston C.B.; He, Yanan; Minick, Douglas J.
Graphical abstract: Abstract: Racemic N -CBZ-3-fluoropyrrolidine-3-methanol (±)-1 was resolved by preparative chiral HPLC. The absolute configuration of the enantiomers of1 was identified by vibrational circular dichroism and confirmed by chemical synthesis, which involved exchanging the CBZ protecting group of (−)-1 with Boc, followed by oxidation with RuCl3, NaIO4, activation of the resulting acid with carbonyl diimidazole and reaction with ( R )-α-methylbenzylamine to give ( R )- tert -butyl 3-fluoro-3-((( R )-1-phenylethyl)carbamoyl) pyrrolidine-1-carboxylate7 . The latter was compared with authentic ( S )- tert -butyl 3-fluoro-3-((( R )-1-phenylethyl)carbamoyl)pyrrolidine-1-carboxylate6 and its diastereomer7 ; the configuration of diastereomer6 was obtained by an X-ray diffraction study. This established that the enantiomer (−)-1 had an ( R )-configuration. Abstract : ( R )-(−)-Benzyl 3-fluoro-3-(hydroxymethyl)pyrrolidine-1-carboxylate: C13 H16 FNO3 [ α ]D 20 = −23 ( c 1.4, CHCl3 ) Source of chirality: resolution Absolute configuration: ( R ) Abstract : ( S )- tert -Butyl 3-fluoro-3-((( R )-1-phenylethyl)carbamoyl)pyrrolidine-1-carboxylate: C18 H25 FN2 O3 [ α ]D 20 = +73 ( c 0.876, MeOH) Source of chirality: resolution Absolute configuration: (3 R, 1′ S ) Abstract : ( R )- tert -Butyl 3-fluoro-3-((( R )-1-phenylethyl)carbamoyl)pyrrolidine-1-carboxylate: C18 H25 FN2 O3 [ α ]D 20 = +63 ( c 0.933, MeOH) Source of chirality: resolution Absolute configuration: (3 R, 1′ R ) Abstract : (−)-( R )-(3-Fluoropyrrolidin-3-yl)methanol: C5 H10 FNO [ α ]D 20 = −4 ( c 1.19, EtOH) Source of chirality: resolution Absolute configuration: ( R ) Abstract : (−)-( R )- tert -Butyl 3-fluoro-3-(hydroxymethyl)pyrrolidine-1-carboxylate: C10 H18 FNO3 [ α ]D 20 = −28 ( c 3.51, CHCl3 ) Source of chirality: resolution Absolute configuration: ( R )